Hypertension in the African American population: A succinct look at its epidemiology, pathogenesis, and therapy - Luis M Ortega (Nefrología, 2015)
Arterial hypertension is prevalent in the black population in the United States. It is directly related to cardiovascular and kidney damage. Its pathogenesis is complex and includes the high incidence of obesity, salt sensitivity and the activation of the renin-angiotensinaldosterone system. This complexity requires a therapeutic combination that includes changes in dietary habits and appropriate antihypertensive regimes. The International Society of Hypertension in Blacks recommends initiating dietary intervention for values of systolic/ diastolic arterial blood pressure above 115/75 mmHg and maintaining arterial blood pressure below 135/85 mmHg using appropiate antihypertensive medication. The most adequate antihypertensive drug for this population has yet to be determined.